2014
DOI: 10.1523/jneurosci.4341-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course of Task-Specific Memory Consolidation Effects in Resting State Networks

Abstract: Previous studies have reported functionally localized changes in resting-state brain activity following a short period of motor learning, but their relationship with memory consolidation and their dependence on the form of learning is unclear. We investigate these questions with implicit or explicit variants of the serial reaction time task (SRTT). fMRI resting-state functional connectivity was measured in human subjects before the tasks, and 0.1, 0.5, and 6 h after learning. There was significant improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
112
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 48 publications
(6 reference statements)
12
112
2
Order By: Relevance
“…7Functional connectivity within a network encompassing cerebellar nuclei, the thalamus, and basal ganglia was significantly greater than at baseline 30 min after exposure to an implicit sequence learning task. Similar connectivity increase was seen for explicit learning; in both cases, this declined after 6 h. From [155] with permission …”
Section: A Systems-level View Of Cerebellar Motor and Cognitive Functsupporting
confidence: 62%
See 2 more Smart Citations
“…7Functional connectivity within a network encompassing cerebellar nuclei, the thalamus, and basal ganglia was significantly greater than at baseline 30 min after exposure to an implicit sequence learning task. Similar connectivity increase was seen for explicit learning; in both cases, this declined after 6 h. From [155] with permission …”
Section: A Systems-level View Of Cerebellar Motor and Cognitive Functsupporting
confidence: 62%
“…Similar connectivity increase was seen for explicit learning; in both cases, this declined after 6 h. From [155] with permission…”
Section: A Systems-level View Of Cerebellar Motor and Cognitive Functsupporting
confidence: 62%
See 1 more Smart Citation
“…They require little 243 processing and are carried out automatically. While they may have been learned explicitly and, 244 during learning, required activation of the PFC and parietal cortex, thus demonstrating top-down 245 control, with practice the roles of the prefrontal and parietal cortices diminish [68][69][70] by inhibiting second messenger cyclic adenosine monophosphate (cAMP) activation [82]. as we will see below, by interacting with DA and NE they also have effects on many cognitive 318 processes.…”
Section: Insert Figure 2 About Here 141mentioning
confidence: 99%
“…Alternatively, cortico-cerebellar connectivity has been indirectly assessed by evaluating changes in somatosensory evoked potentials (SEP) or motor evoked potentials (MEP) (Haavik and Murphy, 2013;Andrew et al, 2015;Baarbé et al, 2014). Recent resting-state fMRI studies revealed increased functional connectivity in cortical and subcortical regions after a short course of motor learning (Vahdat et al, 2011;Ma et al, 2011;Taubert et al, 2011;Tung et al, 2013;Sami et al, 2014). These findings further emphasise the involvement of the cerebellum in motor control and the consolidation of motor memory (Raymond et al, 1996;Inoue et al, 2000;Della-Maggiore et al, 2009).…”
Section: Introductionmentioning
confidence: 99%